2014
DOI: 10.12691/ajps-2-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-administered Lopinavir/Ritonavir and Sulfamethoxazole/Trimethoprim on Reproductive Indices of Male Albino Rats

Abstract: Antiretroviral drugs containing Lopinavir/ ritonavir (LPV/r) are usually co-administered with sulfamethoxazole / trimethoprim (SMX/TMP) in the management of HIV/AIDS and co infections. The concurrent use of these drugs may place more adverse burden on testicular function because reports have associated these drugs individually with decreased testicular function. This study therefore evaluated the effects of the co-administration of SMX/TMP + LPV/r on reproductive indices of male albino rats. Eighty (80) adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Furthermore, there was a significant increase in MDA levels, with a concomitant decrease in GSH, CAT, and SOD activities in HAART-treated animals, hence, proving that the testicular tissue of the untreated rats is greatly affected by ROS due to chemically-induced oxidative stress. Our study supports previous findings that revealed an increase in testicular MDA levels after the administration of HAART drugs (Oputiri & Elias, 2014;Adaramoye et al, 2015). Additionally, the previous study revealed that HAART significantly reduced testicular GSH, SOD, and CAT, consequently reducing antioxidant availability; thereby increasing free radical activity and disrupting the redox balance (Ogedengbe et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, there was a significant increase in MDA levels, with a concomitant decrease in GSH, CAT, and SOD activities in HAART-treated animals, hence, proving that the testicular tissue of the untreated rats is greatly affected by ROS due to chemically-induced oxidative stress. Our study supports previous findings that revealed an increase in testicular MDA levels after the administration of HAART drugs (Oputiri & Elias, 2014;Adaramoye et al, 2015). Additionally, the previous study revealed that HAART significantly reduced testicular GSH, SOD, and CAT, consequently reducing antioxidant availability; thereby increasing free radical activity and disrupting the redox balance (Ogedengbe et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates testicular occurrence of lipid peroxidation. Our result still supports previous findings indicating an increased in testicular MDA levels after the administration of alcohol (Dosumu et al ., ; Sanghishetti et al ., ) or antiretroviral drugs (Oputiri & Elias, ; Adaramoye et al ., ). Mirroring the MDA levels in VCO‐treated groups with alcohol and HAART with glutathione levels, the results represent a mitigation of the negative effects of the former in the protocol which, in this study, is possibly due to the effects of the later (VCO).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] includes a summary of the effects of several CECs grouped as pesticides and pharmaceuticals on male fertility (e.g., hormone levels, testis size and structure, and sperm characteristics) in different species. Example of CECs listed in Table 1 [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] included both in vivo and in vitro treatments and illustrates the broad negative reproductive effects that CECs have.…”
Section: Impact Of Cecs On Male Fertilitymentioning
confidence: 99%
“…Table 1 [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] includes a summary of the effects of several CECs grouped as pesticides and pharmaceuticals on male fertility (e.g., hormone levels, testis size and structure, and sperm characteristics) in different species. Example of CECs listed in Table 1 [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] included both in vivo and in vitro treatments and illustrates the broad negative reproductive effects that CECs have. Overall, collective findings indicate defects in reproductive function across a wide range of marine and terrestrial animals including fish [70], birds [71], alligators, turtles, salamanders [72], mice [73], and panthers [74], when exposed to CECs.…”
Section: Impact Of Cecs On Male Fertilitymentioning
confidence: 99%